2022
DOI: 10.1111/ans.17925
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic onlay mesh at emergency laparotomy: promising early outcomes with long‐acting synthetic resorbable mesh

Abstract: Background: Careful surgical strategy is paramount in balancing the prevention of fascial dehiscence, incisional hernia (IH) and fear of additional mesh-related wound complications post-laparotomy. This study aims to review early outcomes of patients undergoing an emergency laparotomy with prophylactic TIGR ® mesh, used to reduce early fascial dehiscence and potential subsequent IH. Method: A retrospective, ethically approved review of 24 consecutive patients undergoing prophylactic TIGR ® mesh placement durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, in combination with a mesh-mediating traction system, which (by itself) has shown promising results, allowing a safe early abdominal closure [ 28 ]. For example, Alsaadi et al [ 29 ] reported a series of 24 patients requiring emergency laparotomy in whom prophylactic onlay mesh was used. They found that this intervention was associated with acceptable wound-healing outcomes and recommended it as a potential intervention to prevent fascial dehiscence in injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in combination with a mesh-mediating traction system, which (by itself) has shown promising results, allowing a safe early abdominal closure [ 28 ]. For example, Alsaadi et al [ 29 ] reported a series of 24 patients requiring emergency laparotomy in whom prophylactic onlay mesh was used. They found that this intervention was associated with acceptable wound-healing outcomes and recommended it as a potential intervention to prevent fascial dehiscence in injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the large screened to randomized patient ratio implies a high risk of selection bias and limits the external validity of our results. Adding to that, the follow-up time of 1 year for incisional hernia might not be absolutely representative of the incisional hernia rates occurring after emergency midline laparotomy [ 41 , 42 ]. More than half of all screened patients fulfilled the exclusion criterion of previous laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use may be associated with a trend towards increased chronic pain (7.8 per cent) and seroma formation (12.9 versus 6.9 per cent) 11 . Synthetic meshes have been shown to be safe for use even in the setting of peritonitis 10 , and long-acting resorbable biosynthetic meshes, such as TIGR ® matrix mesh (Novus Scientific AB, Uppsala, Sweden), have been used safely for abdominal closure 13 without significant infection or seroma, including in a cohort of high-risk patients undergoing emergency laparotomy 14 . A recent multicentre RCT 15 published in the USA demonstrated significantly lower rates of incisional hernia at 2 years, and median mesh cost, with use of a synthetic mesh (5.6 per cent; US $105/€99) compared with a biological mesh (20.5 per cent; $21 539/€20,280), with no difference in the rates of surgical-site occurrence.…”
Section: Introductionmentioning
confidence: 99%